2020
DOI: 10.3389/fneur.2020.00184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Co-expressed Genes Between Atrial Fibrillation and Stroke

Abstract: Atrial fibrillation (AF) increases the risk of ischemic stroke and systemic arterial embolism. However, the risk factors or predictors of stroke in AF patients have not been clarified. Therefore, it is necessary to find effective diagnostic and therapeutic targets. Two datasets were downloaded from the Gene Expression Omnibus (GEO) database. Differently expressed genes (DEGs) were identified between samples of atrial fibrillation without stroke and atrial fibrillation with stroke. Enrichment analysis of Gene O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Notably, Smurf2 has been reported to be intensively associated with the diagnosis of atrial fibrillation and stroke, which was identified from a protein-protein interaction (PPI) network previously constructed (Zhang et al, 2020 ). Additionally, Smurf2 can enhance neuron differentiation and improve functional recovery from ischemic stroke by ubiquitinating and degrading the EZH2 (Yu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Smurf2 has been reported to be intensively associated with the diagnosis of atrial fibrillation and stroke, which was identified from a protein-protein interaction (PPI) network previously constructed (Zhang et al, 2020 ). Additionally, Smurf2 can enhance neuron differentiation and improve functional recovery from ischemic stroke by ubiquitinating and degrading the EZH2 (Yu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Gene Ontology (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed on Metascape, a powerful annotation tool for the analysis of gene function. 18 , 19 Terms with a p value <0.05, a minimum count of 3 and an enrichment factor >1.5 were collected and grouped into clusters based on their similarities in membership (Kappa scores >0.3). 20 , 21 Thereafter, the top 20 terms for GO or pathway enrichment terms were selected for presentation.…”
Section: Methodsmentioning
confidence: 99%
“…GEO2R is an online useful tool for analyzing DEGs in the GEO platform [16]. The selected criteria in the AMI dataset were set as p-value <0.05 and |log2 FC| >0.5, while in the COPD dataset, the cut-off values were p-value <0.05 and |log2 FC| >1.…”
Section: Screening Of Degsmentioning
confidence: 99%